Prevalence of Batrachochytrium dendrobatidis in Amphibians in Northwestern Italy’s Protected Areas - Arianna Meletiadis; Matteo Riccardo Di Nicola; Stefano Bovero; Marco Favelli; Marzia Pezzolato; Stefania Grella; Giusi Rezza; Pier Luigi Acutis (Animals)
Chytridiomycosis, caused by the fungus Batrachochytrium dendrobatidis (Bd), is a significant threat to global amphibian populations, leading to widespread declines and extinctions. In the spring of 2023, Bd presence was detected in different amphibian species within two protected areas near Turin, Piedmont, Italy, following an unusual mortality event among the common toad (Bufo bufo). Histological and molecular analyses confirmed Bd infection in a deceased Pelophylax sp. specimen, prompting further investigation. Sampling of 166 individuals across seven amphibian taxa revealed an overall Bd occurrence of 38.6%, with Pelophylax sp. showing the highest detection rate (50.5% of 93 individuals). A marked difference in the positivity rate was observed between the two locations, with La Mandria (67.2% of 58) exhibiting significantly higher rates than Vauda (22.9% of 35). While Bd was identified in the sampled amphibians, the exact cause of the observed mortality remains unclear and may involve other pathogens or multifactorial causes, including but not limited to Bd. These findings represent the first documented case of Bd presence in Piedmont after an 18-year gap, highlighting the potential influence of local environmental factors on infection dynamics. The study emphasises the need for expanded, standardised field sampling and further investigation into the various factors affecting amphibian health to guide conservation efforts for vulnerable amphibian species.